Competitiveness of the Spanish and Dutch Greenhouse Industries With the Florida Fresh Vegetable Industry - Daniel J. Cantliffe; John J. Vansickle (EDIS)
This document is HS918, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2003.